2022
DOI: 10.1097/sla.0000000000005780
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy With CAPOX Versus Chemoradiation for Locally Advanced Rectal Cancer With Uninvolved Mesorectal Fascia (CONVERT): Initial Results of a Phase III Trial

Abstract: Objective: To compare neoadjuvant chemotherapy (nCT) with CAPOX alone versus neoadjuvant chemoradiotherapy (nCRT) with capecitabine in locally advanced rectal cancer (LARC) with uninvolved mesorectal fascia (MRF). Background Data: nCRT is associated with higher surgical complications, worse long-term functional outcomes, and questionable survival benefits. Comparatively, nCT alone seems a promising alternative treatment in lower-risk LARC patients with uninvolved MRF. Methods: Patients between June 2014 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…58 59 The pCR rate between neoadjuvant chemotherapy especially mFOLFOXIRI regimen and NACRT is comparable in LARC without mesorectal fascial involved. 60 61 62 However, in view of microsatellite status, MSS rectal cancer is less effective to neoadjuvant chemotherapy compared with MSI-H rectal cancer. 63 More studies with heterogeneous chemotherapy regimens are ongoing which should rise our attention.…”
Section: Clinical Path To Organ Preservationmentioning
confidence: 99%
“…58 59 The pCR rate between neoadjuvant chemotherapy especially mFOLFOXIRI regimen and NACRT is comparable in LARC without mesorectal fascial involved. 60 61 62 However, in view of microsatellite status, MSS rectal cancer is less effective to neoadjuvant chemotherapy compared with MSI-H rectal cancer. 63 More studies with heterogeneous chemotherapy regimens are ongoing which should rise our attention.…”
Section: Clinical Path To Organ Preservationmentioning
confidence: 99%
“…[9,10] PCR rates after neoadjuvant therapy ranged from 10.9% to 32%. [11][12][13][14][15][16] The 5-year disease-free survival (DFS) was 68%, and the 10-year overall survival (OS) was 59.6% for the neoadjuvant chemoradiotherapy group of the German CAO/ARO/AIO-94 Randomized Phase III Trial. [1] Recently, more attention has been given to the total neoadjuvant treatment (TNT) [12,[17][18][19] of LARC and the management of patients with clinical complete response (cCR) by the watchand-wait strategy after nCRT for rectal cancer, [20] but long-term outcomes need to be followed.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] PCR rates after neoadjuvant therapy ranged from 10.9% to 32%. [11–16] The 5-year disease-free survival (DFS) was 68%, and the 10-year overall survival (OS) was 59.6% for the neoadjuvant chemoradiotherapy group of the German CAO/ARO/AIO-94 Randomized Phase III Trial. [1]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the FOWARC study of patients with LARC, treatment with NCT alone resulted in comparable survival to treatment with nCRT alone or nCRT plus NCT 15 . And, in the CONVERT study, NCT alone followed by surgery was found to be an effective alternative to nCRT for patients with LARC and uninvolved mesorectal fascia (MRF) 16 …”
Section: Introductionmentioning
confidence: 99%